Clinical and genetic analysis of Majeed syndrome caused by LPIN2 complex heterozygous mutation and literature review - Wang, Shasha; Yu, Ting; He, Xuelian; Ding, Yan; Wu, Yali (Frontiers in Pediatrics, 2025)
BackgroundMajeed syndrome is a rare autosomal recessive autoinflammatory disorder caused by LPIN2 mutations. It is characterized by chronic recurrent multifocal osteomyelitis (CRMO), congenital dyserythropoietic anemia (CDA), and, in some cases, neutrophilic dermatoses. Its rarity and overlap with juvenile idiopathic arthritis (JIA) often lead to delayed or incorrect diagnoses.Case presentationWe report a 3-year-10-month-old girl with recurrent swelling and pain of the knees and ankles, associated with low-grade fever and elevated inflammatory markers for over two years. Initially diagnosed and treated as JIA with NSAIDs, methotrexate, and adalimumab, she experienced only partial improvement. MRI revealed multifocal bone marrow edema consistent with CRMO, and laboratory results demonstrated mild microcytic anemia. These findings raised suspicion of a monogenic autoinflammatory disease. Whole-exome sequencing identified two novel LPIN2 variants: c.2349del (p.Glu784ArgfsTer8), inherited maternally, and c.2327+3A>G, inherited paternally. RNA analysis confirmed exon 17 skipping, carried out quantitative RT-PCR analysis of LPIN2 mRNA,establishing pathogenicity of the splice-site variant. Together with the clinical features, these findings confirmed the diagnosis of Majeed syndrome. A review of 35 previously reported patients demonstrated that most presented before age three with CRMO and recurrent fever, but the severity of CDA varied widely. IL-1 blockade remains the most effective treatment, with sustained remission reported in multiple cases.ConclusionThis case expands the mutational spectrum of LPIN2 and emphasizes the importance of early genetic testing in children with recurrent osteomyelitis and anemia refractory to standard therapy. Prompt recognition enables accurate diagnosis and timely initiation of IL-1–targeted therapy, which can markedly improve outcomes.